2015
DOI: 10.1093/infdis/jiv233
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Expression Levels in HIV-Uninfected Women Receiving Hormonal Contraception

Abstract: Human immunodeficiency virus (HIV) infectivity increases as receptor/coreceptor expression levels increase. We determined peripheral CD4, CCR5, and CXCR4 expression levels in HIV-uninfected women who used depot medroxyprogesterone acetate (DMPA; n = 32), the levonorgestrel-releasing intrauterine device (LNG-IUD; n = 27), oral contraceptive pills (n = 32), or no hormonal contraception (n = 33). The use of LNG-IUD increased the proportion of CD4 + and CD8 + T cells that expressed CCR5; increases in the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
4
21
0
Order By: Relevance
“…However, a cross sectional study performed by Sciaranghella detected significantly higher CCR5 MFI on CD4 + T cells from Depo-Provera users compared to a control group without hormonal contraception (28). We found a significant increase in integrin α4β7 + CD4 + T cells, and an increasing trend in CCR5 + CD4 + T cells 1 month after Depo-Provera injection compared to baseline or 3 months after Depo-Provera injection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a cross sectional study performed by Sciaranghella detected significantly higher CCR5 MFI on CD4 + T cells from Depo-Provera users compared to a control group without hormonal contraception (28). We found a significant increase in integrin α4β7 + CD4 + T cells, and an increasing trend in CCR5 + CD4 + T cells 1 month after Depo-Provera injection compared to baseline or 3 months after Depo-Provera injection.…”
Section: Discussionmentioning
confidence: 98%
“…One cross-sectional study showed no significant difference in the percentage of CCR5 + CD8 + or CCR5 + CD4 + T cells, but found a significant increase in expression (mean fluorescent intensity, MFI) of CCR5 on CD4 + T cells of Depo-Provera users compared to women not using hormonal contraception (28). TLR-9 stimulation of pDCs resulted in reduced production of TNFα and IFNα in Depo-Provera users compared to women not using hormonal contraception (29).…”
Section: Introductionmentioning
confidence: 99%
“…DMPA-IM has been shown in some clinical studies to increase surface levels of CCR5 on peripheral and female genital tract (FGT) target T cells [55, 56], increase the frequency of CCR5 + T cells in the FGT mucosa [56], decrease the production of several immune modulators by immune cells [57, 58], increase FGT mucosal permeability and expression of barrier function proteins [59] and alter cervicovaginal levels of select secreted immunomodulators [57, 6066]. Several of these studies are consistent with results from animal studies where MPA serum concentrations are similar to those of human DMPA-IM users [59, 6771].…”
Section: Dmpa-sc Vs Dmpa-im: Similar or Different Hiv Acquisition Rimentioning
confidence: 99%
“…6 Studies of the association between HIV acquisition and injectable progestin-only contraceptives use have not reached consistent conclusions, and although progestins have been shown to have a multitude of effects on immune function in vitro, 710 whether these effects are manifest in vivo is unclear. 11,12 …”
Section: Introductionmentioning
confidence: 99%